Written cognate treatment in a Welsh-English bilingual aphasic patient - Polly Barr; Marie-Josephe Tainturier (Frontiers in Psychology, 2015)
Bilingual language representation has been a great source of debate. Cognates are interesting concepts as they share meaning and have close phonology across languages (e.g the Welsh for cat is cath) so it is possible they share part of their representation. Previous spoken cognate treatment has found evidence of generalization across languages (e.g. Kohnert, 2004). There have been limited across language written treatment studies but neither of these have investigated cognates(Roberts, 2011; Tainturier, Roberts, & Roberts, 2011). It remains unknown if written treatment of cognates will also result in a cognate facilitation effect. The purpose of this study is to investigate written picture naming treatment in bilingual patients with aphasia. We will also be investigating the role of homophonolgy in cognate generalization; will generalization (if any) be equal for cognates that have exactly the same phonology (e.g. fig/ffig is pronounced /fIg/) as words that differ in phonology (e.g. cat/cath is /kæt/,/kæθ/).